2018
DOI: 10.3382/ps/pey052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low oxygen during chorioallantoic membrane development on post-hatch growing performance of broiler chickens

Abstract: The prenatal circulatory system is adaptive and capable of plasticity designed for the needs of the growing tissue. When a broiler embryo is faced with hypoxic stress, the process of angiogenesis in tissues begins. Exposure to hypoxic conditions of 17% oxygen during the chorioallantoic membrane (CAM) development (E5 to E12) affected the circulatory system and contributed to an increase in the blood oxygen carrying capacity. The present study aimed to evaluate the effects of hypoxic exposure during CAM developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…For instance, the higher blood glucose level at hatch indicates that more energy was available during the start of life and the higher relative stomach weight could indicate an improved development of the digestive tract. Furthermore, concerning the higher relative heart weight, it can be suggested that during grow-out with a high growth rate, a larger heart might improve provision of oxygen and nutrients to the tissues, and consequently, broiler grow-out performance might be improved ( Molenaar et al., 2011a ; Sozcu and Ipek, 2015 ; Druyan et al., 2018 ). However, grow-out performance at later ages showed opposite results.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the higher blood glucose level at hatch indicates that more energy was available during the start of life and the higher relative stomach weight could indicate an improved development of the digestive tract. Furthermore, concerning the higher relative heart weight, it can be suggested that during grow-out with a high growth rate, a larger heart might improve provision of oxygen and nutrients to the tissues, and consequently, broiler grow-out performance might be improved ( Molenaar et al., 2011a ; Sozcu and Ipek, 2015 ; Druyan et al., 2018 ). However, grow-out performance at later ages showed opposite results.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the findings of Huang et al (2017) showed that chronic hypoxia condition adversely affected survivability, feed conversion ratio and growth in broiler chickens. On the contrary, the findings of Druyan et al (2018) showed that hypoxic conditions did not alter the juvenile growth performance of broiler chickens using a hypoxic condition of 15 or 17% O 2 during a short period of embryonic development. The authors reported that hypoxic conditions improved the body weights of the birds at the market age.…”
Section: Ventilationmentioning
confidence: 86%
“… Effect of hypoxia (17 or 15% O 2 ) on feed conversion ratio [adapted from Druyan et al (2018) ]. FCR, feed conversion ratio.…”
Section: Ventilationmentioning
confidence: 99%
“…Increasing oxygen concentration to 27.5% during mid and late incubation phase improved this situation and increased broiler hatching weight ( Zhang et al, 2008 ). In contrast, exposing embryos to a low oxygen (17%) environment at E5–E12 increased 7D broiler body weight, a positive effect that lasted until 28D, and increased breast muscle production ( Druyan et al, 2018 ). This occurred probably because the low-oxygen environment stimulated the embryonic vasculature to develop in a good direction and to better deliver nutrients to the pectoral muscle, ( Hadad et al, 2014 ), thus promoting posthatch muscle development.…”
Section: Physiological Processes Of Muscle Fiber Developmentmentioning
confidence: 98%
“…It was demonstrated that lighting and thermal adjustment during the incubation phases improves the number and activity of satellite cells, promotes muscle fiber development, increases the embryonic muscle fiber area ( Zhang et al, 2014 ) and improved meat quality ( Piestun et al, 2013 ). Incubation of chicken embryos in a hypoxic environment with 17% oxygen content improves posthatch broiler body weight and increases pectoral muscle production ( Druyan et al, 2018 ). Green light exposure during broiler incubation increased the number and proliferative activity of myogenic and satellite cells, promoted embryonic muscle fiber development ( Bai et al, 2019 ), and increased pectoral muscle production ( Zhang et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%